A systematic literature review of the use and effectiveness of the Computer Assisted Rehabilitation Environment for research and rehabilitation as it relates to the wounded warrior. - Collins, John-David; Markham, Amanda; Service, Kathrine; Reini, Seth; Wolf, Erik; Sessoms, Pinata (Work, 2015)
BACKGROUND: Several U.S. military treatment and research facilities employ a Computer Assisted Rehabilitation Environment (CAREN) [Motek Medical BV, Amsterdam, The Netherlands] for research and rehabilitation of complex injuries exhibited by Wounded Warriors. There has been little scientific evidence of the effectiveness of this type of system for rehabilitation. OBJECTIVE: A systematic review of the literature was completed to determine what type of work has been performed on the CAREN and report findings of clinical significance. METHODS: Specific terms were searched on electronic databases to include journal articles, abstracts, and peer-reviewed conference proceedings related to the CAREN. RESULTS: Twenty-six publications were elicited that met our criteria. These were divided by their primary focus: rehabilitation, clinical research, and technical reports. DISCUSSION: Results from published articles have determined that the system is a capable tool for both assessment and rehabilitation, but little has currently been published, particularly on patient populations. CONCLUSION: More research needs to be performed to evaluate its effectiveness as a rehabilitation tool compared to other rehabilitation methods. It is expected that a system, such as the CAREN, will challenge patients multifactorially (e.g. physically and cognitively) and provide biofeedback while decreasing rehabilitation time and increasing effectiveness of treatment.